Upaya Meningkatkan Pemahaman Konsep Materi dalam Muatan Bahasa Indonesia Menggunakan Video Interaktif di Kelas II SDN 64/ 1 Muara Bulian - Ouralita, Silvi; Safitri, Eny; Fazliani, Bella; Budiman, Soleh; Destrinelli, Destrinelli (TSAQOFAH, 2023)
Indonesian language learning should involve the active role of students directly, so that students will interact using the media that has been presented by the teacher. Observations made in the field found a problem, namely students lack of focus and lack of understanding of the concept of material in Indonesian language content. The purpose of writing this journal is to analyze related efforts to improve understanding of material concepts in Indonesian content by using interactive videos in class II SDN 64/1 Muara Bulian. The type of research used is PTK (Classroom Action Research). This research was conducted at SD Negeri 34/I Teratai, in class II to be precise. The results obtained are that students are still confused when using interactive videos, and are more comfortable when the teaching process is carried out using traditional methods, namely by using a blackboard that is devoted to providing subject matter related to how to write cursive in stories by paying attention to the use of capital letters. The conclusion is that the use of interactive videos in increasing students' understanding of concepts in Indonesian language subjects with non-continuous writing material in stories with attention to the use of capital letters is effective at the elementary school level.